2020
DOI: 10.1186/s12871-020-00973-4
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative Dexmedetomidine for outpatient cataract surgery: a systematic review

Abstract: Background: Cataract surgery is one of the most common procedures performed worldwide in the elderly. Various medications can provide effective anesthesia and analgesia for cataract surgery, but undesirable side effects limit the utility of each medication or combination of medications. Dexmedetomidine may serve as an anesthesia adjunct for outpatient cataract surgery in the elderly. Methods: Searches were conducted in Cochrane, Embase, and PubMed for randomized clinical trials investigating the use of dexmede… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 32 publications
1
18
1
1
Order By: Relevance
“…A recent systematic review on dexmedetomidine for cataract surgery also obtained similar findings of reduction in IOP, higher pain relief, and higher patient satisfaction but relatively more cardiovascular depression and longer recovery discharge time (15). It was also reported that there were many inconsistencies in dosages, methods of administration, and outcome analysis in RCTs on dexmedetomidine and concluded that, instead of routine use, dexmedetomidine should be considered only in individual conditions after careful evaluation (15). Overall, published studies suggest that whichever method is utilized, a lower dose should be used to minimize undesirable adverse effects.…”
Section: Doses and Methods Of Administrationmentioning
confidence: 61%
See 4 more Smart Citations
“…A recent systematic review on dexmedetomidine for cataract surgery also obtained similar findings of reduction in IOP, higher pain relief, and higher patient satisfaction but relatively more cardiovascular depression and longer recovery discharge time (15). It was also reported that there were many inconsistencies in dosages, methods of administration, and outcome analysis in RCTs on dexmedetomidine and concluded that, instead of routine use, dexmedetomidine should be considered only in individual conditions after careful evaluation (15). Overall, published studies suggest that whichever method is utilized, a lower dose should be used to minimize undesirable adverse effects.…”
Section: Doses and Methods Of Administrationmentioning
confidence: 61%
“…Other administration methods include intramuscular injection 45 min before surgery (35) and intranasal route in children (36,37). A recent systematic review on dexmedetomidine for cataract surgery also obtained similar findings of reduction in IOP, higher pain relief, and higher patient satisfaction but relatively more cardiovascular depression and longer recovery discharge time (15). It was also reported that there were many inconsistencies in dosages, methods of administration, and outcome analysis in RCTs on dexmedetomidine and concluded that, instead of routine use, dexmedetomidine should be considered only in individual conditions after careful evaluation (15).…”
Section: Doses and Methods Of Administrationmentioning
confidence: 78%
See 3 more Smart Citations